Functional optimization of light-activatable Opto-GPCRs: Illuminating the importance of the proximal C-terminus in G-protein specificity - Leemann, Siri; Kleinlogel, Sonja (Frontiers in Cell and Developmental Biology, 2023)
Introduction: G-protein coupled receptors (GPCRs) are the largest family of human receptors that transmit signals from natural ligands and pharmaceutical drugs into essentially every physiological process. One main characteristic of G-protein coupled receptors is their ability to specifically couple with different families of G-proteins, thereby triggering specific downstream signaling pathways. While an abundance of structural information is available on G-protein coupled receptorn interactions with G-proteins, little is known about the G-protein coupled receptor domains functionally mediating G-protein specificity, in particular the proximal C-terminus, the structure which cannot be predicted with high confidentiality due to its flexibility. Methods: In this study, we exploited OptoGPCR chimeras between lightgated G-protein coupled receptors (opsins) and ligand-gated G-protein coupled receptors to systematically investigate the involvement of the C-terminus steering G-protein specificity. We employed rhodopsin-beta2-adrenoceptor and melanopsin-mGluR6 chimeras in second messenger assays and developed structural models of the chimeras. Results: We discovered a dominant role of the proximal C-terminus, dictating G-protein selectivity in the melanopsin-mGluR6 chimera, whereas it is the intracellular loop 3, which steers G-protein tropism in the rhodopsin-beta2-adrenoceptor. From the functional results and structural predictions, melanopsin and mGluR6 use a different mechanism to bovine rhodopsin and b2AR to couple to a selective G-protein. Discussion: Collectively, this work adds knowledge to the G-protein coupled receptor domains mediating G-protein selectivity, ultimately paving the way to optogenetically elicited specific G-protein signaling on demand.